2021
DOI: 10.3390/en14102786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Influence of Cetane Improver Additives on the Outcomes of a Diesel Engine Characteristics Fueled with Peppermint Oil Diesel Blend

Abstract: This paper aims to evaluate the impact of cetane improvers on the combustion, performance and emission characteristics of a compression ignition engine fueled with a 20% peppermint bio-oil/diesel blend (P20). It is hypothesized that the low viscosity and boiling point of peppermint oil could improve the atomization characteristics of the fuel. However, the usage of peppermint oil is restricted due to its low cetane index. To improve this, Diethyl Ether (DEE) and Di- tertiary Butyl Peroxide (DTBP) are added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The engine performances; power and torque as well as the increase in SFC efficiency as shown in pictures gb1 and gb2 are the addition of ED as an additive. This reason is supported by several studies reported [56][57][58][59][60][61]. That, in general, additives have a decreasing effect on the density of biodiesel fuel and an increase in the cetane index.…”
Section: Methodssupporting
confidence: 54%
“…The engine performances; power and torque as well as the increase in SFC efficiency as shown in pictures gb1 and gb2 are the addition of ED as an additive. This reason is supported by several studies reported [56][57][58][59][60][61]. That, in general, additives have a decreasing effect on the density of biodiesel fuel and an increase in the cetane index.…”
Section: Methodssupporting
confidence: 54%
“…The results of the studies presented in three papers validate the alternative fuel additives [1,4,5]. Fabiś et al [1] present the potential of dimethyl ether as fuel for SI engines.…”
Section: Contributions In This Issuementioning
confidence: 65%
“…Fabiś et al [1] present the potential of dimethyl ether as fuel for SI engines. Paneerselvam et al [4] evaluate peppermint bio-oil as an additive applied as a cetane improver. Cisek et al [5] prove the synergy effect between examined additives which manifested in greater reduction in nitrogen oxides and particulate matter, while using both additives together compared to individual use.…”
Section: Contributions In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…As a setback for these fuels, they all lack to attain a higher cetane value. 7,8 It is well-known that diesel engines need a moderate cetane number to have lower ignition delays and efficient combustion processes. Thus, a lower cetane value directly affects the ignition delay period of the fuel being used in a diesel engine.…”
Section: Introductionmentioning
confidence: 99%